A systems engineering approach for the deployment of an atmospheric monitoring station - Venter, Andrew Derick (My University, 2015)
Atmospheric monitoring is a vital part of environmental management. Monitoring temporal changes in atmospheric pollution on a local, regional and global scale is important in order to mitigate adverse effects on health and the environment. Currently there is general agreement that atmospheric pollution should be monitored, however, less emphasis is often placed on what should be achieved and the specific monitoring that should be included. Atmospheric pollution monitoring is often hampered by geographically restricted and site specific effects resulting in inefficient or ineffective information transfer to the local manager. The scientific community in the developed world often underestimate problems associated with the maintenance of comprehensive atmospheric measurement stations in Africa. A holistic approach is needed to optimise atmospheric monitoring according to specifications set out by system design; this includes site selection, site design, maintenance and quality control. The aim of this dissertation is to apply the Systems Engineering approach to a case study, the Welgegund atmospheric measurement station (WAMS), to offer a holistic view of interaction between different operational systems and the complexity behind their management in order to be informative to students and personnel from a non-engineering background. A knowledge gap exists that links practical industry related sciences such as engineering to more fundamental and theoretical sciences. In this dissertation the customer need was determined and an operational concept was developed for the WAMS system. The high level goals of the WAMS were derived and stated as applicable to other new as well as established measurement stations. Technical and fundamental requirements such as trained staff for appropriate logistical support and a broad spatial coverage of air quality monitoring were identified. The system boundaries and operational constraints were established for the WAMS, exposing weaknesses and proposing solutions to ensure long term sustainability. Weaknesses include irregular funding periods and retention of expertise (trained students leave academia for industry) whereas a possible solution included overlapping projects and contracts. Functional analysis highlighted the design and establishment process of the WAMS. Physical architectures and interfaces were explored and finally the success of the establishment of the WAMS was evaluated by a reliability block diagram. The reliability of the WAMS system was calculated to be 96.6 %. This agrees well with the percentage data coverage calculated for the gaseous (95.9 %), aerosol (93.4 %) and meteorological (94.6 %) systems (15 min averages). The reliability of the national grid to supply power to the WAMS was found to be the main restrictive component. It may be a challenge interacting and coordinating projects with different disciplines, branches or sectors outside of a speciality project. This study has bridged the gap between industry related sciences such as engineering to more fundamental and theoretical sciences. A framework has been provided that highlights the techniques of Systems Engineering and provides an understanding for the need and process of atmospheric monitoring.
MIng (Development and Management Engineering), North-West University, Potchefstroom Campus, 2015
Keywords: Systems Engineering; Atmospheric monitoring; Operational Concept; Functional analysis; Welgegund atmospheric measurement site